2017
DOI: 10.1177/0333102417704187
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of craniofacial pain

Abstract: Aim To provide an overview of mechanisms underlying craniofacial pain; to highlight peripheral and central adaptations that may promote chronification of pain in craniofacial pain states such as migraine and temporomandibular disorders (TMD). Background Pain is a common symptom associated with disorders involving craniofacial tissues including the teeth and their supporting structures, the temporomandibular joint and the muscles of the head. Most acute painful craniofacial conditions are easily recognized and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
114
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(120 citation statements)
references
References 108 publications
(156 reference statements)
0
114
0
6
Order By: Relevance
“…The ability of CNS areas to undergo neuroplastic changes represents an integral process underlying functions as seemingly diverse as memory, cognition, somatosensation and sensorimotor functions. Neuroplasticity occurring in a particular CNS area may be associated with plasticity of nonneural cells, such as glia (ie, "glioplasticity") and in fact glia can influence the expression of neuroplasticity, for example as shown in the case of processes underlying memory and in trigeminal central sensitisation which is a feature of acute or chronic oro-facial pain states (for review, see refs [61][62][63]. Given the focus of this article, the following centres on the role that plasticity in one particular CNS area, the sensorimotor cortex, play in oro-facial sensorimotor functions.…”
Section: Plasticity Of the Sensorimotor Cortex And Its Role In Adapmentioning
confidence: 99%
“…The ability of CNS areas to undergo neuroplastic changes represents an integral process underlying functions as seemingly diverse as memory, cognition, somatosensation and sensorimotor functions. Neuroplasticity occurring in a particular CNS area may be associated with plasticity of nonneural cells, such as glia (ie, "glioplasticity") and in fact glia can influence the expression of neuroplasticity, for example as shown in the case of processes underlying memory and in trigeminal central sensitisation which is a feature of acute or chronic oro-facial pain states (for review, see refs [61][62][63]. Given the focus of this article, the following centres on the role that plasticity in one particular CNS area, the sensorimotor cortex, play in oro-facial sensorimotor functions.…”
Section: Plasticity Of the Sensorimotor Cortex And Its Role In Adapmentioning
confidence: 99%
“…In addition, outputs from the thalamus can be directed to other cortical and limbic structures that are responsible for processing the cognitive, affective, and emotional components of pain. 1,12,13 In addition, the activation of mesencephalic and bulbar structures can modulate nociceptive processing. The main inhibitory descending pathway includes structures such as the periaqueductal gray matter (GM) and the rostral ventromedial medulla (RVM), which projects to the VBSNC where the nociceptive responses are modulated.…”
mentioning
confidence: 99%
“…Previous studies have shown that the peptide EPQ(pY)EEIPIA may bind to the SH2 domain of SFKs and thereby activate the kinases (Liu et al, ; Xu, Doshi, Lei, Eck, & Harrison, ). Delivering 1 mM of the peptide into cultured neurons (Yu, Askalan, Keil, & Salter, ) or 5 mM of the peptide into hippocampal neurons in brain slice preparations (Chichorro, Porreca, & Sessle, ) significantly enhances SFK‐mediated neuronal activity. In this work, we investigated effects of the peptide EPQ(pY)EEIPIA delivered into neurons on the firing activity.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we investigated effects of the peptide EPQ(pY)EEIPIA delivered into neurons on the firing activity. Since the peptide EPQ(pY)EEIPIA is not membrane‐permeant (Liu et al, ; Xu et al, ), to examine the effect of direct activation of SFKs, the peptide was delivered into ARC neurons through recording electrodes filled with the internal solution containing the EPQ(pY)EEIPIA (1 mM) (Chichorro et al, ; Feng et al, ; Yu et al, ).…”
Section: Resultsmentioning
confidence: 99%